2008
DOI: 10.1016/s1472-6483(10)60320-3
|View full text |Cite
|
Sign up to set email alerts
|

Stable embryonic stem cell lines in rabbits: potential small animal models for human research

Abstract: Although embryonic stem (ES) cell lines derived from mice and primates are used extensively, the development of such lines from other mammals is extremely difficult because of their rapid decline in proliferation potential and pluripotency after several passages. This study describes the establishment of rabbit ES cell lines with indefinite proliferation potential. It was found that the feeder cell density determines the fate of rabbit ES cells, and that maximum proliferation potential was obtained when they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 39 publications
2
81
1
2
Order By: Relevance
“…3). Rabbit pluripotent stem cells were defined as EpiSC-type or primed state stem cells; these are rarely competent to contribute to blastocyst chimeras and are therefore developmentally and functionally distinct from naive state mouse ES cells (15,25,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Rabbit pluripotent stem cells were defined as EpiSC-type or primed state stem cells; these are rarely competent to contribute to blastocyst chimeras and are therefore developmentally and functionally distinct from naive state mouse ES cells (15,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Cells Induced by RA and SB431542-Previously, we have detected in vitro differentiated neurons and astrocytes in spontaneously differentiated rabbit pluripotent stem cells (15,25,28). Using this method, rabbit pluripotent stem cells were first induced to form EBs by suspension culture and then allowed to differentiate in the presence of FBS.…”
Section: In Vitro Differentiation Of Rabbit Es Cells Into Neural Lineagementioning
confidence: 99%
See 1 more Smart Citation
“…These rabbit ESCs were morphologically similar to primate ESCs, whereas their growth rate resembled closely to mESCs (Wang et al 2007). Another study showed that the success of rabbit ESCs is determined by the feeder cell density on which they are cultured (Honda et al 2008). Rabbit ESCs reached their full pluripotency potential, similar to hESCs, when they were cultured on feeder cells with one-sixth of the density compared to the density upon confluency (Honda et al 2008).…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%
“…Another study showed that the success of rabbit ESCs is determined by the feeder cell density on which they are cultured (Honda et al 2008). Rabbit ESCs reached their full pluripotency potential, similar to hESCs, when they were cultured on feeder cells with one-sixth of the density compared to the density upon confluency (Honda et al 2008). It has also been observed that rabbit ESCs rely on signalling pathways similar to hESCs to remain pluripotent, such as bFGF and Activin/Nodal signalling (Honda et al 2009).…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%